Las zonas de diáspora. La traducción según Susana Romano Sued - Claudia Elina Rosa (Cuadernos LIRICO)
In this paper we approach the works written by Susana Romano Sued, semiologist, poet, translator, and literary theorist, who proposes a conceptual network around the politics and poetics of translation that goes beyond the studies of comparative literatures. In her works emerge the linguistic, philosophical studies, and the Jewish tradition in which she was born. Romano proposes translation as the stage of the diaspora that becomes the formation of literary and cultural identities. It is investigated from a psychoanalytic perspective in the operation of processing the grieving of the translation of an original displaced and deferred. Facing the melancholy of the impotence of the translation Susana Romano Sued proposes the conceptualization of literature translated as a genre that coexists with all genres of a literary system.